Understanding Dynamic Electrical Material through Discovery Learning: Does it impact learning outcomes? - Boby Syefrinando; Al Fajri Adha; Ayu Sofna; Cici Pramita; Tasa Ratna Puri; Mona Erliza; Fauzan Sulman (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to determine the effect of the discovery learning model on student learning outcomes in dynamic electrical material. This research uses a quantitative type of research using pre-experimental methods. The population in this study consisted of all students in class XII MIPA at SMAN 13 Bungo for the 2023/2024 academic year. The sample in this study amounted to 33 people, of which the number of students was 18 people, while the number of female students was 15 students. This research was obtained from the results of students' daily test scores on dynamic electricity material. The instrument in this research consists of essay questions in the form of an essay test. These questions are given to students when doing daily tests on dynamic electricity material. Based on the results of students' daily tests, the data obtained an average value of 72.16 with a standard deviation of 10.133. Based on the research results above, it can be concluded that the discovery learning model does not have a significant effect on student learning outcomes in dynamic electricity material. This is because the process of implementing the discovery learning model has not run optimally so it has not been able to maximize and improve learning outcomes, especially dynamic electrical material.